Penerapan Metode ARAS untuk Menentukan Kelayakan Perpustakaan Sekolah Diakreditasi - Sukamto; Elfizar; Roni Salambue; Aidil Fitriansyah; Evfi Mahdiyah (Politeknik Caltex Riau, 2023)
School libraries should be accredited with the aim of improving the quality of libraries. Pekanbaru City Library and Archives Service (DISPUSIP) in determining a school library that deserves to be accredited is still done manually, namely DISPUSIP went directly to the field to monitor the library in the school and the data collection still used manual entries. Meanwhile, a lot of data must be collected, causing the data to be inaccurate and take a long time. For this reason, a decision support system is needed. The data used are nine junior high schools both public and private as an alternative. While the criteria refer to the school library accreditation instrument issued by the National Library consisting of six criteria, namely collections, library facilities and infrastructure, library services, library staff, library administration and management, and reinforcement. Data analysis using the ARAS method. The results of the study are that Sek 4, Sek 5 and Sek 2 are school libraries that are eligible for accreditation